Organization and Management of a System of Pedagogical Activity in Professional Education (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Implementation of a number of changes in the conditions of professional education in terms of content, quantity and quality of education, educational programs, and technology. The implementation of this production is to provide a positive solution to the development of the economy, the production of poverty, the production of poverty, and the improvement of the well-being of young people and our youth.